Solid state physics : Structure and properties of materials - Wahab, M. A. (New Delhi: Narosa Publishing House, 2005)
Solid State Physics: Structure and Properties of Materials 2nd Edition, authored by M. A. Wahab, is a comprehensive book for students of pure and applied sciences and other engineering disciplines. It contains a brief summary at the end of each chapter with definitions of important terms. The solved examples in the text help students revise better for exams.
Bibliography 588-590p.; Index 591-596p.
Keywords: Atomic bonding; Atomic diffusion; Solid state physics; Physics